2013
DOI: 10.1002/ajmg.a.36123
|View full text |Cite
|
Sign up to set email alerts
|

Maternal FMR1 premutation allele expansion and contraction in fraternal twins

Abstract: Fragile X syndrome results from an expansion of the CGG trinucleotide repeat in the 5' untranslated region of the Fragile X Mental Retardation 1 (FMR1) gene. Expansion of a maternal premutation allele is the mechanism by which a full mutation allele arises; contraction of a maternal premutation allele is rare. Here we report on both an expansion and contraction of a maternal FMR1 premutation allele in fraternal twins. The propositus was the product of a 29-week gestation twin pregnancy and was referred for FMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Contracted alleles detected in FXS families in a non-mosaic state have already been reported by us, in an unaffected boy who inherited an allele of 43 CGGs derived from a large PM (around 190 CGGs) carried by his mother [21]. Similar reverted and non-mosaic alleles have been described in FXS families both in unaffected females [19,22] and in unaffected males [23,24]. Contracted alleles in the range of normality have also been detected along with expanded ones in FXS mosaic males, such as in the four affected boys reported by Maia et al [25], who inherited the normal allele by their FM or PM mother, or as in a monozygous male twin, who derived the normal allele from his PM mother [26].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Contracted alleles detected in FXS families in a non-mosaic state have already been reported by us, in an unaffected boy who inherited an allele of 43 CGGs derived from a large PM (around 190 CGGs) carried by his mother [21]. Similar reverted and non-mosaic alleles have been described in FXS families both in unaffected females [19,22] and in unaffected males [23,24]. Contracted alleles in the range of normality have also been detected along with expanded ones in FXS mosaic males, such as in the four affected boys reported by Maia et al [25], who inherited the normal allele by their FM or PM mother, or as in a monozygous male twin, who derived the normal allele from his PM mother [26].…”
Section: Discussionsupporting
confidence: 81%
“…Despite the fact that contraction events were reported to be independent of AGG presence [8], in the present cases, the two reverted alleles derived from maternal expanded CGG repeats without AGG interruptions. In other published cases of contracted alleles, AGG interruptions were absent except for one female who inherited a 54 CGG grey zone allele by her mother, carrier of a 93 CGG PM [19]. In a recent paper, a model for CGG instability has been refined studying 5508 transmissions alleles from males and females [20].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of these retractions is unknown but may be due to excision of the expanded FM or PM CGG repeat in the early postzygotic period, producing mosaic normal size/grey zone size (GZ 45-54 CGGs)/PM/FM results with tissue variability. Most notably, Alfaro et al reported both expansion and contraction of a maternal PM (93 CGGs) carrier in fraternal twins in the postnatal setting [ 18 ]. This report detailed dizygous twins where the male twin demonstrated a FM expansion and the female twin showed a retraction of the mother’s PM allele to the GZ range (54 CGGs).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst a number of cases of contractions into the grey zone or normal range have been previously reported [ 16 , 18 , 21 , 23 ], this is the first study to provide postnatal follow-up (repeat sizes, methylation in multiple tissues and FMR1 mRNA levels in blood) of a normal sized allele in a male twin (with a FM female sibling). Retraction to the normal CGG size in a male twin of a PM mother is an important finding in prenatal diagnosis that should not be underestimated and may be underdiagnosed due to testing regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Vits et al [27] reported a contraction from 110 CGG repeats in the mother to 44 CGG repeats in her daughter [27]. In Alfaro et al [51], a mother's premutation (93 CGG repeats) expanded to > 200 CGG repeats in one male and contracted to 54 CGG repeats in a female twin [51]. Tabolacci et al [25] described the case of reversion from a maternal premutation allele of about 190 CGG repeat to a normal size allele of 43 CGG repeats in the male child.…”
Section: Discussionmentioning
confidence: 96%